Preliminary Assessment of Optimized Accessorial Roof Shape for Performance of Wind Turbine Mounted on Eco-Roof System - Wang, Xiao Hang; Chong, Wen Tong; Wong, Kok Hoe; Wang, Chin Tsan; Saw, Lip Huat; Poh, Sin Chew; Lai, Sai Hin (Springer Verlag, 2018)
Transition from conventional energy paradigm to sustainable energy system is a major challenge in 21st century. This article presents a preliminary shape analysis of an accessorial roof with wind turbine to maximize the utilization of wind energy. This investigation focuses on the optimized accessorial roof shape to assess the performance of wind turbines mounted on an eco-roof. The optimization included inclination angle analyses of different variations of accessorial roofs and wind turbine power coefficient through numerical simulation. A V-shape accessorial roof with inclination angle of 19.5° is identified as the most effective roof inclination angle for wind energy harvesting which is due to a 63% wind speed-up and a lower turbulence intensity. The V-shape accessorial roof is capable of augmenting power output of a wind turbine installed on the building to about 1.375 times higher than that of 0.3366 without V-shape accessorial roof structure. A short straight channel integrated with the accessorial roof can further enhance the efficiency of the wind energy harvesting. This accessorial roof offered the possibility of harvesting wind energy in low wind speed areas. This design is also integrated with a solar photovoltaic system, daylight saving system, and rain water harvesting system. Finally, the power generated from the wind turbines of eco-roof system was estimated.